Comparative study of sulfonated branched and linear poly(phenylene)s polymer electrolyte membranes for fuel cells. (8th March 2018) - Ahmed, Faiz; Sutradhar, Sabuj Chandra; Ryu, Taewook; Jang, Hohyoun; Choi, Kunyoung; Yang, Hanmo; Yoon, Sujin; Rahman, Md. Mahbubur; Kim, Whangi
Abstract: Branched and linear sulfonated poly(phenylene)s (BSPs and LSPs, respectively) polymer electrolyte membranes (PEMs) containing benzophenone moiety were successfully synthesized and the performance of the LSPs and BSPs were compared in conjunction with Nafion 211 ® . The LSPs and BSPs were synthesized by the CC coupling polymerization reaction between 1, 4-dichloro-2, 5-dibenzoylbenzene (PBP) and 1, 4-dichloro-2-benzoylbenzene, and from PBP, 1, 4-dichloro-2-benzoylbenzene, and 1, 3, 5-trichlorobenzene (branching agent), respectively. The degree of sulfonation in both LSPs and BSPs were controlled by varying the concentrations of chlorosulfonic acid and the structures of the resultant PEMs were confirmed by 1 H-NMR spectroscopy. The optimal LSP (LSP-2) and BSP (BSP-2) PEMs showed excellent chemical stability due to the absence of ether linkages in the polymer backbone, while the BSP-2 exhibited better proton conductivity (94.6 mS/cm under 90% relative humidity at 80 °C), water resistivity, and lower dimensional changes compared to the LSP-2, which is comparable to Nafion 211 ® . The maximum power density for BSP-2 and LSP-2 were 0.60 and 0.49 W/cm 2, respectively, while it was 0.62 W/cm 2 for Nafion 211 ® . Membrane properties were studied with regard to ion exchange capacity, dimensional stability, proton conductivity, thermogravimetric analysis, and water uptake. The surface morphology of membranes was also analyzed by atomic force microscope. Highlights: Branched and linear sulfonated (BSP and LSP, respectively) polymer electrolyte membranes (PEMs) were synthesized. The properties and the performance of the synthesized PEMs were compared in conjunction with Nafion 211 ® . The optimal BSP showed better proton conductivity, physical, and chemical stability than LSPs. The power density in fuel cells based on optimized BSP, LSP, and Nafion 211 ® were 0.60, 0.49 and 0.62 W/cm 2, respectively.